Engineering design of artificial vascular junctions for 3D printing. (20th June 2016) - Han, Xiaoxiao; Bibb, Richard; Harris, Russell
Abstract: Vascular vessels, including arteries, veins and capillaries, are being printed using additive manufacturing technologies, also known as 3D printing. This paper demonstrates that it is important to follow the vascular design by nature as close as possible when 3D printing artificial vascular branches. In previous work, the authors developed an algorithm of computational geometry for constructing smooth junctions for 3D printing. In this work, computational fluid dynamics (CFDs) is used to compare the wall shear stress and blood velocity field for the junctions of different designs. The CFD model can reproduce the expected wall shear stress at locations remote from the junction. For large vessels such as veins, it is shown that ensuring the smoothness of the junction and using smaller joining angles as observed in nature is very important to avoid high wall shear stress and recirculation. The issue is however less significant for capillaries. Large joining angles make no difference to the hemodynamic behavior, which is also consistent with the fact that most capillary junctions have large joining angles. The combination of the CFD analysis and the junction construction method form a complete design method for artificial vascular vessels that can be 3D printed using additive manufacturing technologies.